Road back to glory : how the NCAA Football video game franchise could make a comeback - Pond, Addison; Cocco, Adam R.; Spencer, Tyler C. (London : SAGE Publications: SAGE Business Cases Originals, 2020)
The NCAA Football video games were extremely popular, with the last installment, NCAA Football 14, selling around 1.5 million copies. In 2015, however, the United States Court of Appeals ruled that the National Collegiate Athletic Association violated federal antitrust laws by failing to compensate athletes for the use of their likenesses in the video games, marking the end to this popular video game. Recent developments from California's state legislature and the National Collegiate Athletic Association Board of Governors may clear a path for NCAA Football to return. However, revitalization of the franchise is not guaranteed. This case asks readers to examine legal issues surrounding NCAA Football and to consider solutions to allow the game to return to the market.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; NCAA football -- Case studies; Antitrust law -- United States -- Case studies; Video games industry -- Cases